Construction Site: Farming Strong, All Year Long - Rinker, Sherri Duskey; Ford, AG (San Francisco, California : Chronicle Books, 2022)
"Told in rhyming text, six farm vehicles work through all the seasons, from spring planting to building a barn to protect the animals in winter."--
Keywords: Farm trucks -- Juvenile fiction; Construction equipment -- Juvenile fiction; Farms -- Juvenile fiction; Stories in rhyme; Farm trucks -- Fiction; Construction equipment -- Fiction; Farm life -- Fiction; Stories in rhyme; Stories in rhyme